PERANCANGAN KOMIK EDUKASI RETAK - AIDIL PUTRA, Drs. Syafwan, M.Si., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Aidil Putra: Designing Educational Comic "Retak". Final assignment ofVisual Communication Design Major, Fine Arts Department, Faculty ofLanguages and Arts, Padang State University.Divorce happens in a family and it has direct impact to the children, itcauses the negative psychology to occcur in the children's way of thinking.Divorce rate in West Sumatera is still high with different problems a nddifferent family background.Based on the problems mentioned above, Educational Comic "Retak" isdesigned. Comic is chosen as the prime media, because it can conveymeaning effectively and the message can be directly understood withoutdeeper thinking compare to text book and novel. Compared to novel,comic has advantage on its visualisation.The comic design is supported with (1) family theory, (2) divorce theory,(3) design theory and (4) comic theory. The support of distinct theorieswill perfect the design of educational comic "Retak".In designing this comic, the writer used 5W1H methods (what, where,when, who, why, how). The writer did an analysis on Educational comic"Retak" that has not been made before, as the review on designing thecomic, it is also supported with some media such as x-banner, poster, tshirt,pins, sticker, bookmark, and key chain which can promote theEducational Comic "Retak".Key search: West Sumatera, Reatk, Educational Comic